IPO8 and FBXL10: New Reference Genes for Gene Expression Studies in Human Adipose Tissue - Pozo, Carmen Hurtado; Calvo, Rosa M.; Vesperinas‐García, Gregorio; Gómez‐Ambrosi, Javier; Frühbeck, Gema; Corripio‐Sánchez, Ramón; Rubio, Miguel A.; Obregon, Maria‐Jesus (Obesity (Silver Spring, Md.), 2010)
Housekeeping genes frequently used in gene expression studies are highly regulated in human adipose tissue. To ensure a correct interpretation of results, it is critical to select appropriate reference genes. Subcutaneous (SC) and omental (OM) adipose tissue expression was analyzed from lean and obese subjects using whole genome complementary DNA (cDNA) microarrays to identify stably expressed genes and commercial TaqMan low density arrays (LDAs), with 16 common control genes. The best candidate gene from microarrays analysis was F‐box and leucine‐rich repeat protein‐10 (FBXL10) (fold‐change 10−3 P < 0.01), an ubiquitous nucleolar protein evolutionarily conserved. Hypoxanthine phosphoribosyltransferase 1 (HPRT1) and importin 8 (IPO8), were the best reference genes among the 16 genes in the LDAs with coefficient of variation (CV) of 4.51 and 4.55%, respectively. However, when the LDAs data were further analyzed by the geNorm and NormFinder softwares, IPO8, a nuclear protein mediating import of proteins, was the first and the third better reference gene, respectively. IPO8 and FBXL10 were further validated by real‐time PCR in additional OM and SC fat samples and primary cultured preadipocytes. According to their CV, IPO8 resulted more suitable than FBXL10 in both adipose tissue depots and SC preadipocytes, whereas FBXL10 performed better than IPO8 in OM cultured preadipocytes. Both genes expression levels did not change throughout adipogenesis. Thus, we provide clear evidence that IPO8 and FBXL10 are good candidates to use as reference genes in gene expression studies in human OM and SC adipose tissues as well as differentiated primary preadipocytes.